Islamic Inclusivism: Insights From Abu Dhabi, Silaturahmi Tunnel, and Walisanga-Ende - Hendrikus Maku; Asep Saepudin Jahar; Stephen Bevans; Ambros Leonangung Edu (Changing Societies & Personalities)
This article responds to the claim that Islam is a religion of violence, which has fostered a generation afflicted with Islamophobia. To support their argument, the authors present several historical instances that showcase Islam’s benevolent aspects. These historical instances, elaborated upon in this article, include the Abu Dhabi Brotherhood Declaration (A Document on Human Fraternity for World Peace and Living Together), the Silaturahmi Tunnel connecting the Istiqlal Mosque and the Catholic Cathedral of Jakarta, and the interreligious cooperation occurring at the Walisanga Islamic Boarding School in Ende, Flores. Quraish Shihab’s Quranic exegesis serves as an analytical tool to examine these three instances. Data were collected through documentation, participant observation, and interviews, then qualitatively analyzed. Through this methodology, the study demonstrates that Islamic ethics and inclusive communal life have manifested an inclusive nature within Islam. By employing this selected method, the study demonstrates how elements of Islamic ethics and the ongoing inclusive communal life ingrained among people illustrate the inclusive nature of Islam.